(untitled) (Revista LIDER, 2020)
In the course of the last years, the tourism sector has turned, for many regions of the world, into a major source of employment creation, of foreign currencies flows and a decisive stimulus to investment and economic growth. Caleta Tortel (coastal locality of the Aysen region, Chile), has not been foreign to this impact, while turning into a tourist destination, that has gradually caught the interest of national and foreign tourists who visit the region. This fact is demonstrated in the pattern of tourist flows. However, since the influx of tourists to pristine zones, these face big challenges in order to achieve an ecologically balanced and sustainable development for this type of destinations. In this context, to know the principal tourist markets is of vital importance, since it helps with some key processes: the structuringofanofferbasedontheprincipal motivations that these visitors present; allowing an appropriate management of the destination; protecting and managing natural and cultural resources; supporting development of strategies for a sustainable form of tourism, with a focus on local development, where the endogenous agents are those who lead this process.